The Embodied Mind: Cognitive Science and Human Experience - Rosch, Eleanor; Thompson, Evan; Varela, Francisco J. (Cambridge, Massachusetts MIT Press, 1993)
The Embodied Mind provides a unique, sophisticated treatment of the spontaneous and reflective dimension of human experience. The authors - argue that only by having a sense of common ground between mind in Science and mind in experience can our understanding of cognition be more complete. Toward that end, they develop a dialogue between cognitive science and Buddhist meditative psychology and situate it in relation to other traditions such as phenomenology and psychoanalysis.Francisco Varela is Director of Research at the Centre National de Recherche Scientifique and Professor of Cognitive Science and Epistemology, CREA, at the Ecole Polytechnique in Paris. Evan Thompson is Assistant Professor of Philosophy at the University of Toronto. Eleanor Rosch is Professor of Psychology at the University of California, Berkeley.
Keywords: 21st Century (2001-2100); Corporeality; Philosophy